2014
DOI: 10.1002/cyto.a.22507
|View full text |Cite
|
Sign up to set email alerts
|

Efficient purification of CD4+ lymphocytes from peripheral blood progenitor cell products using affinity bead acoustophoresis

Abstract: Processing of peripheral blood progenitor cells (PBPC) for clinical transplantation or research applications aims to effectively isolate or deplete specific cell populations, utilizing primarily magnetic or fluorescence activated sorting methods. Here, we investigated the performance of microfluidic acoustophoresis for the separation of lymphocyte subsets from PBPC, and present a novel method for affinity-beadmediated acoustic separation of cells which can otherwise not be acoustically discriminated. As the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Finally, novel label-free sorting techniques based on biophysical properties have been recently reported for the sorting of MSC subpopulations in culture. 61 Other alternatives are ultrasound-based techniques, which are currently being investigated in our laboratory 62,63 and which can possibly be applied to purify pre-and postculture clinical MSC products.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, novel label-free sorting techniques based on biophysical properties have been recently reported for the sorting of MSC subpopulations in culture. 61 Other alternatives are ultrasound-based techniques, which are currently being investigated in our laboratory 62,63 and which can possibly be applied to purify pre-and postculture clinical MSC products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both piezo-actuators (trapping and levitation) were characterized by admittance analysis using an impedance analyzer (Z-Check 16777k, Sinephase, Austria), see Fig. 1A- [8][9]. Hence, both the resonance frequencies and Q-factors of the piezo-actuators were calculated from electrical impedance measurements, and were used as starting values before manual fine tuning of the driving frequency based on experimental observations.…”
Section: Methodsmentioning
confidence: 99%
“…Given the rarity of SSCs and the complexity of bone marrow tissue, none of these papers described a technology that would be suitable for SSC isolation. Finally, only one publication reports a high throughput (300,000 cells/min) (Lenshof et al, 2014), of the order of magnitude required for SSC isolation from a bone marrow buffy coat which can comprise up to a hundred million cells. Thus, acoustophoresis may not demonstrate the throughput required for sorting SSCs from bone marrow harvests.…”
Section: Acoustophoresismentioning
confidence: 99%
“…The authors also demonstrated that the progenitor cells retained viability and maintained their colony-forming ability post-sorting. The same group used immunomagnetic beads to alter the acoustic properties of the cells to achieve improved separation (Lenshof et al, 2014). CD4 + lymphocytes were separated from RBC-depleted PBPC samples with 87% purity and separation efficiencies of 65%, comparable to MACS.…”
Section: Acoustophoresismentioning
confidence: 99%
See 1 more Smart Citation